(untitled) (Scientia Agricola, 2007)
The Citrus Variegated Chlorosis and the Coffee Leaf Scorch are some of the many destructive diseases caused by Xylella fastidiosa, a gram-negative bacterium limited to the xylem of affected plants. As its genetic characterization is still not well established, different isolates of X. fastidiosa from citrus and coffee were evaluated through RAPD (Random Amplified Polymorphic DNA) technique to characterize and classify these isolates based on similarity coefficients. Sixteen isolates of X. fastidiosa were used on this trial, obtained from citrus, coffee and almond. The genetic polymorphism evaluation was performed using six arbitrary 10-base primer pairs. It was possible to establish a dendogram in which the isolates were classified into five groups (A, B, C, D and E). A prevalence of citrus isolates in groups A and D was observed. In groups B and C, there was a prevalence of coffee isolates meanwhile the group D consisted of the almond isolate, solely.